KINETIKA ADSORPSI LOGAM Cu DAN Zn PADA LIMBAH CAIR KELAPA SAWIT MENGGUNAKAN MEMBRAN SILIKA: ABSORPTION KINETIC OF Cu AND Zn METALS IN PALM LIQUID WASTE USING SILICA MEMBRANE - Feni Sri Erani; Abu Hasan; Indah Purnamasari (KINETIKA, 2022)
Heavy metals can cause environmental pollution and affect human health. Cu and Zn are often found in the environment. One method to reduce Cu and Zn is to use the adsorption method. Adsorption has become a competitive method in the field of wastewater. Adsorption kinetics is one of the main factors that must be understood before the application of any adsorbent. In each adsorption process, linear or non-linear analysis of the kinetics was applied. A fit index (correlation coefficient or sum of squares) was applied to access the best model. The purpose of this study was to determine the adsorption equation model, to obtain the adsorption kinetics of Cu and Zn metals using a silica membrane. The methodology used is silica extraction by precipitation method and then the process of making PVA and PEG membranes as adhesives and solvents. For the analysis of metal concentrations of Cu and Zn, Atomic Absorption Spectrophotometry (AAS) was used, while for membrane morphology analysis, a Scanning Electron Microscope (SEM) was used. From the process of applying silica membrane to palm oil liquid waste, the results of Pseudo Order 1 absorption kinetics for Cu metal (artificial solution) with k value of artificial Cu metal (4M) 0.0596, and k value of artificial Cu metal (8M) 0.0022, while the Pseudo Order 1 absorption kinetics for Zn metal with a k value of Zn metal (4M) 0.0077, and a k value of Zn metal (8M) 0.0109.